LITERATURE AND CINEMA IN THE SHORT STORY “ESCOLA DE HERÓIS”, BY IDELMA RIBEIRO DE FARIA - Franco, Arnaldo [UNESP] (Universidade Federal do Para, 2022)
The short story “Escola deheros”, by the São Paulo writer Idelma Ribeiro de Faria, was one of the winners of the National Contest of Contos do Paraná, in 1978, being published in the book The Winners: 1978 – Concurso Nacional de Contos do Paraná in the same year. year. In this short story, the literary narrative incorporates cinematographic narrative procedures (editing, cutting, scene) to the narration in order to, through the narrated story, criticize militarism – a strong feature of its historical context, both particular (the civil-military dictatorship in Brazil) and general (the 20th century marked by wars). In this communication, we will analyze and interpret the short story, approaching the literary and cinematographic languages that constitute it as a narrative.
LITERATURA E CINEMA NO CONTO “ESCOLA DE HERÓIS”, DE IDELMA RIBEIRO DE FARIA
Keywords: Idelma Ribeiro de Faria; Movie theater; School of heroes; Tale